Development and validation of a composed canine simulator for advanced veterinary laparoscopic training - Oviedo-Peñata, Carlos A.; Giraldo Mejía, Gloria E.; Riaño-Benavides, Carlos Humberto; Maldonado-Estrada, Juan G.; Lemos Duque, Juan D. (Frontiers in Veterinary Science, 2022)
The development of innovative simulation models for veterinary laparoscopic surgery training is a priority today. This study aimed to describe a didactic simulation tool for the training of total laparoscopic gastropexy (TLG) with intracorporeal sutures in dogs. CALMA Veterinary Lap-trainer composite simulator (CLVTS) was developed from a plaster cast of 2 Great Dane canines mimicking the space and the correct position to carry out a TLG. After video instruction, 16 veterinarians with different degrees of experience in minimally invasive surgery (Experts, n=6 and intermediates, n=10) evaluated four sequential simulating TLG with intracorporeal suturing in the CLVTS. Subsequently, they completed an anonymous questionnaire analyzing the realism, usefulness, and educational quality of the simulator. The CLVTS showed a good preliminary acceptance (4.7/5) in terms of the usefulness and adequacy of the exercises that, in the participants' opinion, are appropriate and are related to the difficulty of the TLG. In addition, both experienced and intermediate surgeons gave high marks (4.5/5) to the feeling of realism, design, and practicality. There were no significant differences between the responses of the two groups. The results suggest that the CVLTS has both face and content validity. Where it can be practiced in a structured environment for the development of a total laparoscopic gastropexy with intracorporeal suture and without compromising patient safety, but still has some limitations of the scope of the study. Further studies are needed to establish the ability to assess or measure technical skills, including the degree of transferability to the actual surgical environment.